Pergeseran Penghidupan dan Agensi Perempuan - Dewi, Elisabeth; Ayunda, Dyah; Andalas, Patrisius; Lede, Yulita (Parahyangan Center for International Studies, 2024)
In the last two decades, Sumba Island has experienced a shift in livelihood patterns after the extension of four regencies in the region. The change was initiated by Indonesia's development program through agro-industrial expansion in areas considered less fertile. In addition, the hilly characteristics of the region with vast grasslands and also the traditions of the Marapu indigenous people in Sumba have attracted the attention of the tourism industry. Therefore, indigenous communities have experienced a shift in land ownership systems and some of them have shifted to livelihood strategies of small farm management to non-agricultural activities, such as mining or becoming migrant workers. These changes also affect the gender division of labor and also the symbolic values of Sumba's indigenous people, such as weaving activities carried out by women. They utilize the skills they have acquired over generations to respond to these conditions and support their family's and community’s resilience. To understand changes in livelihood conditions, the meaning of symbols, and women's narratives, this research uses qualitative methods within the Sustainable Livelihood Framework with an ecofeminism perspective. This research discusses how the agency of women weavers in responding to changes in livelihood patterns amid the implementation of capitalist-patriarchal oriented development programs. The findings of this study show that the agency and activism of women weavers are influenced by affective historical factors by adapting the symbolic value of weaving customs into economic and emancipatory values. Keywords: livelihood, women weavers, family, community, agency, development programs.